Isolation, identification, and in vitro predatory activity of nematophagous fungus Arthrobotrys musiformis and its interaction with nematodes using scanning electron microscopy - Cao, Xin; Xu, Qiang; Wan, Xue-Mei; Yang, Xue-Cai; Jia, Xiao-Ye; Xue, Xu-Jia; Du, Jiang-Long; Cai, Kui-Zheng (Biocontrol science and technology, 2018)
We isolated and identified nematophagous fungus Arthrobotrys musiformis from materials derived from cattle and sheep. We also molecularly characterised the native fungal isolates and evaluated the nematophagous activity of the isolates. A total of 19 isolates of A. musiformis were isolated from 1532 samples, and the detection rate of A. musiformis in all samples was 1.24%. These isolates were identified using a light microscope and their 5.8S rDNA, 18S rDNA, 28S rDNA, and the internal transcribed spacers 1 and 2 region. Interaction of the isolate (NPS045) with the nematode targets of the infective larvae (L 3 ) of Haemonchus contortus and the free-living nematode Caenorhabditis elegans was observed by scanning electron microscopy (SEM). SEM result showed that the two species of nematodes were initially captured at 5 h after being added to the isolates. L 3 was penetrated at 22 h after capture and completely destroyed by the fungus at 68 h. C. elegans was penetrated at 14 h post-capture and was completely digested by the fungus at 24 h. In vitro experimental assay of samples in 24-well plates showed that for the three fungal isolates, the L 3 s of Trichostrongylus colubriforms were reduced by 94.80%, 90.17%, and 89.02%.